The Role of Digital Crowdfunding Platforms in Enhancing Financial Inclusion in Arab Countries: A Case Study of Algeria and Egypt in Light of the Saudi Model - Kheira messaoudi (Journal of Excellence for Economics and Management Research, 2026)
This study aims to analyze the role of digital crowdfunding platforms in enhancing financial inclusion in Algeria and Egypt, taking the Saudi model as a benchmark for comparison in light of the rapid development of financial technology (FinTech). The study adopts a descriptive-analytical approach combined with a comparative econometric methodology using panel data for the period (2018–2024) to assess the impact of regulatory and technological variables on financial access. The findings reveal that crowdfunding has a substantial capacity to reduce financing costs; however, its effectiveness varies across the sample countries. The Saudi experience outperforms due to the maturity of regulatory frameworks, particularly regulatory sandboxes, and a higher level of digital trust. In contrast, the impact in Algeria and Egypt remains constrained by legislative gaps and weak digital financial literacy.The study recommends adopting flexible regulatory frameworks, strengthening the governance of digital platforms, and integrating digital financial education into national policies to ensure sustainable financial inclusion